Knowledge Acquisition in Nepalese Telecom Industry - Kandel, Laxman Raj (NCC Journal, 2019)
This research paper presents the Knowledge Management practice in Nepalese telecom sector. This study is based on cross section analysis of 85 observations for analyzing relationship between the knowledge management (KM) practices status in Nepalese telecom sector. The methodology used by Kohli (1993) and Daroch (2003) has been used for the research. Survey instruments we reorganized into one part and five factors. Spearman Rank Correlation, Analysis of variance (ANOVA), Cranach’s alpha etc. is used for data analysis. The valid response rate of 70 % was found. Among the factors that designed for knowledge acquisition, information input- employee has less mean score and information input-financial has high mean score than the others factors. In case of Information input-competitors, Nepalese telecom industry analyzes the financial contribution of their products or services. Employees of Nepal telecom has rated higher mean value in the KM practices i.e. knowledge acquisition, which means Nepal telecom appeared good in KM practices than Ncell. There is a significant difference between Nepal telecom and Ncell in term of the knowledge acquisition. Nepal telecom has better KA (Knowledge Acquisition) practices. Correlation matrix was computed to assess the extent or degree of relationship in between the factors or the research variables.